2017
DOI: 10.1111/avj.12637
|View full text |Cite
|
Sign up to set email alerts
|

Survey of systemic antimicrobial prescribing for dogs by Victorian veterinarians

Abstract: Antimicrobial drug selection for treatment of dogs by registered veterinarians in Victoria was generally consistent with recent recommendations, although some details were widely variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…This contrasts to regional-specific guidelines (AIDAP) for amoxicillin or AMC 9. In a recent survey of antimicrobial prescribing habits of veterinarians within our region, amoxicillin and AMC were the most routinely prescribed empirical antimicrobial for canine UTIs at 10% and 71%, respectively 23. These two antimicrobials had the highest level of resistance towards E. coli in this study.…”
Section: Discussionmentioning
confidence: 49%
“…This contrasts to regional-specific guidelines (AIDAP) for amoxicillin or AMC 9. In a recent survey of antimicrobial prescribing habits of veterinarians within our region, amoxicillin and AMC were the most routinely prescribed empirical antimicrobial for canine UTIs at 10% and 71%, respectively 23. These two antimicrobials had the highest level of resistance towards E. coli in this study.…”
Section: Discussionmentioning
confidence: 49%
“…Treatment of acute diarrhea in dogs is another condition where antimicrobial use is often excessive [ 5 ]. One survey in the United Kingdom [ 9 ] and another in Australia [ 10 ] found that 71% and 32% of veterinarians, respectively, prescribed antimicrobials for non-complicated gastroenteritis cases before resorting to other more recommended options, such as nutritional management and deworming, and/or probiotics, with or without antidiarrheal agents. Because most potentially enteropathogenic bacteria are also isolated from clinically healthy dogs, the American College of Veterinary Internal Medicine (ACVIM) expert group recommendation is to only use supportive therapy [ 5 ] and avoid using antimicrobials for uncomplicated cases of acute diarrhea (even hemorrhagic).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with results of previous reports. [37][38][39] In a study from Denmark, even when looking only at the subgroup of guideline-users (a group of veterinarians expected to be interested in prudent antimicrobial use), only 39% stated to frequently perform culture and sensitivity testing before treating a UTI. 11 The same study found the main barriers for veterinarians to perform culture and sensitivity testing to be good experiences with empiric treatments and owners' financial concerns.…”
Section: Discussionmentioning
confidence: 99%